PEMANFAATAN SELULOSA ECENG GONDOK (Eichhornia crassipes) SEBAGAI BAHAN DASAR PEMBUATAN NITROSELULOSA - Abdul Halim; Andi Setiawan; Arif Andriyanto; Syahrul Bachtiar (JSSHA ADPERTISI JOURNAL, 2021)
Water hyacinth is a plant that lives on the surface of the waters and swamps. Those rapid breed of it considering its as weeds community. The water hyacinth fibers has only been used as raw material for handicrafts, biogas and paper raw materials. This research was conducted to determine the cellulose nitrasion reaction effect and its reaction temperature from water hyacinth on the quality of nitrocellulose production. This research was divided on to two stages, nitrocellulose production and nitrogen levels detection in nitrocellulose. Nitrogen detection were carried out using the Fourier Transform InfraRed (FTIR) analysis and mikro-Kjeldalh method. The research results showed that the highest production of -NO2 in nitrocellulose was achieved at reaction temperature of 30 0C and needed the reaction time 30 minutes. In those conditions, optimum -NO2 level in nitrocellulose from water hyacinth cellulose material was achieve 16.76% N value according to mikro-kjeldhal methode and 11.5% absorption value according to FTIR analysis at wavelength of 1550-1570 cm-1